The legal research methodology as a method for researching in business area: A case study applied to gymnasiums - Aldeia, Susana (2024)
Purpose – The main objective of this paper is to understand how the analysis of laws and jurisprudence influences the decisions of gym managers in Portugal. Design/methodology/approach – For this purpose, the Portuguese tax law was investigated, particularly the Value Added Tax law and additional legal dispositions. It also researches the arbitral case law related to nutrition consulting in sports activity companies. Findings – The nutrition consultation is considered a medical act subject to the legal disposition of article 9º of the Value Added Tax Code, which means that when the medical service is provided by a professional, the beneficiary of the services can benefit from the VAT exemption. This disposition observes the European Union Directive 2006/112/EC of the European Council. Nevertheless, when a nutritionist provides these services through an entity that offers sports activities like gyms, some doubts are raised because it can be considered that nutritional monitoring has no therapeutic purpose. Customers could not benefit from the VAT exemption if some conditions were not observed. The arbitral tax court has been considering that it needs to keep some requirements for that exemption could be applied to the gym services. In several cases, fulfilling the conditions is complex and generates litigation between the Portuguese Tax Authority and gyms. In the personal sphere, there are two possibilities for the service's recognition i) if the service is recognized as a consultation, it could benefit as a medical expense in the personal income tax statement; ii) if it is not considered as a medical expense, each person can deduct 15% of the VAT in the same statement. Originality: This paper demonstrates the role that court rulings play in clarifying day-to-day issues for managers. It also shows that laws and court rulings are an essential source of data in management research. Research limitations/implications – This study only analyses the Portuguese case, it could be interesting to study other countries that do not apply the value-added tax law.